2014
DOI: 10.1007/s12035-014-8893-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mitochondrial Fusion and Fission Modulation in Sporadic Parkinson’s Disease

Abstract: Accumulating data suggests that mitochondrial deficits may underline both sporadic and familial Parkinson's disease (PD) neurodegenerative process. Impairment of mitochondrial dynamics results in reactive oxygen species (ROS) production, decreases mitochondrial membrane potential, and could potentiate the accumulation of dysfunctional mitochondria. Excessive mitochondrial fragmentation is associated with the pathology of sporadic PD. Therefore, we modulated mitochondria fusion and fission in different sporadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 63 publications
1
54
0
1
Order By: Relevance
“…For example, mitochondrial deficits appear early in mouse models of AD (Du et al, 2010; Yao et al, 2009). Consistent with the basic research, deficits in the balance of mitochondrial fusion/fission have been reported in neurodegenerative diseases such as AD and Parkinson's disease (Santos et al, 2015; Wang et al, 2009). Understanding this process and protecting mitochondrial integrity may provide a strategy for improving the health and function of the aging brain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, mitochondrial deficits appear early in mouse models of AD (Du et al, 2010; Yao et al, 2009). Consistent with the basic research, deficits in the balance of mitochondrial fusion/fission have been reported in neurodegenerative diseases such as AD and Parkinson's disease (Santos et al, 2015; Wang et al, 2009). Understanding this process and protecting mitochondrial integrity may provide a strategy for improving the health and function of the aging brain.…”
Section: Discussionsupporting
confidence: 79%
“…A balance between fusion vs. fission is also necessary for limiting the production of toxic reactive oxygen species (ROS) and for normal cellular metabolism, whereas disruptions in these processes affect the cell and may be implicated in neurodegenerative diseases (Santos et al, 2015; Wang et al, 2009; D.B. Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The original postmortem finding was a decrease in complex I activity in the substantia nigra of PD patients, and subsequently, the activities of other respiratory chain complexes have been shown to be decreased to a variable extent in the platelets and skeletal muscles of PD subjects 115117. Furthermore, mitochondrial fusion and fission, responsible for the dynamic morphology and functional quality of the organelle, are possibly altered in sporadic PD, as suggested from studies in cell-based models of this disease, including cybrids 5,118,119. Cybrids are created by the fusion of human neuroblastoma cells or teratocarcinoma cells depleted of endogenous mitochondrial DNA (mtDNA) with platelets from PD subjects 119,120.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Typically, the overproduction of amyloid beta (Ab) in the postmortem brains of AD patients was indicated to induce imbalances in mitochondrial fission and fusion processes 42,43 . Finally, imbalances in mitochondrial dynamics were also observed in ALS models 44,45 . Several enzymes in the brain have been shown to contribute to the production of ROS/RNS.…”
Section: Ros/rns-mediated Oxidative Stressmentioning
confidence: 85%